Climate response of the Florida Peninsula to Heinrich events in the North Atlantic. (15th August 2018) - Arnold, T. Elliott; Diefendorf, Aaron F.; Brenner, Mark; Freeman, Katherine H.; Baczynski, Allison A.
Abstract: Hydrogen and carbon isotope values (δD & δ 13 C) were measured on lipid biomarkers from a sediment core collected in Lake Tulane, Florida, USA, to infer shifts in climate and hydrologic variables during the Last Glacial. Isotopic trends from 24 samples correlate with plant community shifts evaluated in a previous pollen study by Grimm et al. (2006). We observe maxima in Δleaf values and minima in δD values concurrent with peaks in Pinus pollen abundances and Heinrich Events 4-2. Increased Δleaf values during North Atlantic cold spells indicate lower water-use-efficiency among angiosperms around Lake Tulane. Combined δD values from terrestrial and aquatic lipids, confirm that aridity decreased during cold, stadial periods (Heinrich Events), and increased during warm, interstadials. Furthermore, lower δD values in aquatic lipids during stadials are attributed to warming, as well as changing moisture sources. The anti-phase relationship between temperatures and aridity derived from our subtropical lacustrine record and those at high latitude in the North Atlantic is likely the result of complex ocean-atmosphere teleconnections that resulted from the collapse of Atlantic Meridional Overturning Circulation during Heinrich Events in the North Atlantic. Highlights: Shifts in δD and δ 13 C values of plant biomarkers from a Florida lake correspond to Heinrich Events 4-2. Carbon isotope values indicate more precipitation in Florida during Heinrich Events. Hydrogen isotope values indicate more precipitation, and less arid conditions during Heinrich Events. Lower δD values in aquatic biomarkers during Heinrich Events are attributed to warming and changing moisture sources.